Increasing Body Mass Index, Blood Pressure, and Acanthosis Nigricans Abnormalities in School-Age Children. (December 2013) - Otto, Debra E.; Wang, Xiaohui; Garza, Viola; Fuentes, Lilia A.; Rodriguez, Melinda C.; Sullivan, Pamela
This retrospective quantitative study examined the relationships among gender, Acanthosis Nigricans (AN), body mass index (BMI), and blood pressure (BP) in children attending school Grades 1–9 in Southwest Texas. Of the 34, 897 health screening records obtained for the secondary analysis, 32, 788 were included for the study. A logistic regression analysis was carried out with AN as the dependent variable, with year, gender, BMI, and BP as independent variables. The results indicate that the rate of children in each grade with three positive markers increased 2% during a 3-year period between 2008 and 2010. In the 5-year period between 2005 and 2010, a clear trend of significantly higher numbers of children with both AN and BMI markers was apparent. Gender played a significant role as females were more likely to have the AN marker than males. Further study is indicated based on the increasing trend of school-age children in Texas with positive markers for AN, increased BMI and BP.